-S-QUAL, CUSTOMER SATISFACTION, AND LOYALTY INTENTION OF MY BLUE BIRD AN OFFLINE TO ONLINE EXPANSION OF A TAXI BUSINESS - Pratiwi, Lintang; Aprianingsih, Atik (Journal of Business and Management, 2018)
Abstract.Â In this modern era where transportation takes a big role in helping people to deal with their activities, online transportation comes up with the purpose to make the transportation process become much more easier. Blue Bird is the only conventional taxi company that offers online reservation system. They wants to sustain and gain loyal customers. The purpose of this research is to determine e-service quality relation with customer satisfaction towards My Blue Bird app. An online questionnaire was spread to 245 respondents. The finding of this study shown that there is significant relationship between efficiency and customer satisfaction, and significant relationship between customer satisfaction to loyalty intention. However, there are also insignificant relationship between system availability and privacy towards customer satisfaction.Â Keywords: E-S-QUAL, Customer Satisfaction, Loyalty Intention, Online Transportation